2021
DOI: 10.3389/fpsyg.2021.611867
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Production Rates in Music and Speech

Abstract: Individuals typically produce auditory sequences, such as speech or music, at a consistent spontaneous rate or tempo. We addressed whether spontaneous rates would show patterns of convergence across the domains of music and language production when the same participants spoke sentences and performed melodic phrases on a piano. Although timing plays a critical role in both domains, different communicative and motor constraints apply in each case and so it is not clear whether music and speech would display simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…Previous studies that quantified many hours and a high variety of music and speech recordings showed distinct peak AM rates: music peaks at 1-2 Hz and speech peaks at 3.5-5.5 Hz (Ding et al, 2017;Poeppel & Assaneo, 2020;Varnet et al, 2017). Consistent with those findings, these rate differences are also observed in spontaneous speech and music production (Pfordresher et al, 2021). Next, temporal regularity of AM could also be important, as music is often metrically organized with an underlying beat, whereas speech is not periodic and is better considered quasi-rhythmic (Kotz et al, 2018;Poeppel & Assaneo, 2020).…”
Section: Introductionsupporting
confidence: 80%
“…Previous studies that quantified many hours and a high variety of music and speech recordings showed distinct peak AM rates: music peaks at 1-2 Hz and speech peaks at 3.5-5.5 Hz (Ding et al, 2017;Poeppel & Assaneo, 2020;Varnet et al, 2017). Consistent with those findings, these rate differences are also observed in spontaneous speech and music production (Pfordresher et al, 2021). Next, temporal regularity of AM could also be important, as music is often metrically organized with an underlying beat, whereas speech is not periodic and is better considered quasi-rhythmic (Kotz et al, 2018;Poeppel & Assaneo, 2020).…”
Section: Introductionsupporting
confidence: 80%
“…This result indicates that auditory perception seems to activate rate-specific temporal processing mechanisms with different sweet spots in the speech and music domain. This is consistent with previous research indicating that speech signals exhibit temporal modulations at faster rates than music signals (Ding et al, 2017) and studies showing faster spontaneous production rates in speech than in music (Pfordresher et al, 2021). Our results are indicative of the speech and music stimuli in a perception task triggering the activation of their respective motor systems, resulting in the observed differences in optimal time scales.…”
Section: Tone and Speech Perception Triggers Two Different Time Scalessupporting
confidence: 93%
“…Previous studies that quantified many hours and a wide variety of music and speech recordings showed distinct peak AM rates in the modulation spectrum: music peaks at 1 to 2 Hz and speech peaks at 3.5 to 5.5 Hz [ 19 21 ]. Consistent with those findings, these rate differences are also observed in spontaneous speech and music production [ 22 ]. Next, temporal regularity of AM could also be important, as music is often metrically organized with an underlying beat, whereas speech is not periodic and is better considered quasirhythmic [ 20 , 23 ].…”
Section: Introductionsupporting
confidence: 86%